Circ_0000189 Promotes the Malignancy of Glioma Cells via Regulating miR-192-5p-ZEB2 Axis. (19th September 2022) - Yang, Jian; Hou, Guoqiang; Chen, Hongjin; Chen, Weilin; Ge, Jianwei
Abstract : Background . Some recent studies have reported the role of circular RNAs (circRNAs) in modulating the tumorigenesis of human malignancies. Nevertheless, the expression characteristics, biological functions, and regulatory mechanism of circ_0000189 in glioma are unclear. Methods . Quantitative real-time polymerase chain reaction (qRT-PCR) was utilized to detect the expression levels of circ_0000189, miR-192-5p, and ZEB2 mRNA in glioma tissues and cells. The association between the expression of circ_0000189 and the clinicopathological indicators and the features of magnetic resonance imaging (MRI) images of glioma patients were analyzed. Western blot was utilized to evaluate ZEB2 expression and epithelial-mesenchymal transition (EMT-)-related proteins (E-cadherin, N-cadherin, as well as Vimentin) in glioma cells. Cell proliferation was assessed employing cell counting kit-8 (CCK-8) and EdU experiments. Flow cytometry was used to detect the apoptotic rate of the cells. Cell migration and invasion were accessed employing Transwell assay. Moreover, dual luciferase reporter gene assay and RNA immunoprecipitation assay were employed to investigate the targeting relationship between miR-192-5p and circ_0000189, miR-192-5p, and ZEB2. Subcutaneous tumorigenesis experiment and lung metastasis experiment in nude mice were conducted to verify the regulatory function of circ_0000189 on the proliferation and metastasis of glioma cells in vivo . Results . circ_0000189 was markedly overexpressed in glioma tissues and cell lines. Its high expression was associated with poor clinical pathological indicators and adverse MRI signs. Gain-of-function experiments and loss-of-function experiments confirmed that circ_0000189 overexpression facilitated the proliferation and migration, as well as invasion of glioma cells, and suppressed apoptosis, and facilitated epithelial-mesenchymal transition (EMT) process. Compared to the control group, knocking down circ_0000189 suppressed the malignant phenotypes of glioma cells both in vivo and in vitro . Working as a competitive endogenous RNA, circ_0000189 directly targeted miR-192-5p, and repressed its expression, and circ_0000189 positively modulated ZEB2 expression indirectly via repressing miR-192-5p. Conclusion . circ_0000189 facilitates the progression of glioma by modulating miR-192-5p/ZEB2 axis.